2019
DOI: 10.3389/fimmu.2019.00859
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in IL-33-Induced STAT6-Dependent Type 2 Airway Inflammation

Abstract: Sex differences in asthma prevalence are well-documented but poorly understood. Murine models have contributed to our understanding of mechanisms that could regulate this sex disparity, though the majority of these studies have examined responses present after Th2 adaptive immunity is established. We have now investigated how sex influences acute activation of innate cell populations in the lung upon initial exposure to the model antigen, ovalbumin (OVA), in the presence of IL-33 (OVA+IL-33), to prime the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Moreover, female mice were more sensitive to OVA, based on diarrhea score, allergy score, and serum OVA-IgE levels. Previous studies have shown that blunted IL-13 production in males may protect against OVA-A and that a reduced percentage of Treg cells in female mice is important for the development of the OVA allergic immune response. , As the mortality of mice increased with more than five OVA-A, we suggest that female mice should be intraperitoneally injected four times with 50 μg of OVA to successfully establish an OVA-sensitive mouse model.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, female mice were more sensitive to OVA, based on diarrhea score, allergy score, and serum OVA-IgE levels. Previous studies have shown that blunted IL-13 production in males may protect against OVA-A and that a reduced percentage of Treg cells in female mice is important for the development of the OVA allergic immune response. , As the mortality of mice increased with more than five OVA-A, we suggest that female mice should be intraperitoneally injected four times with 50 μg of OVA to successfully establish an OVA-sensitive mouse model.…”
Section: Discussionmentioning
confidence: 59%
“…This indicates a potential increased responsiveness of female AMs to comparable levels of IL-33, 31 which is supported by female biases in the response to exogenous IL-33 administration. 64 In order to determine whether any of the observed differences between sexes were due to differential uptake of MWCNT, phagocytosis was measured by flow cytometry; side scatter (SSC) values are reported to be proportionate to the relative amount of nanoparticles phagocytosed by cells. [65][66][67][68][69] The AM SSC observed at both 24 h and 7 days post-MWCNT exposure were not significantly different between sexes (Figure 1C).…”
Section: Sex Differences In Nuclear Er Expression Correspond To Sex D...mentioning
confidence: 99%
“…Sex selection of experimental animals needs to be based on the goals and limitation that exists in a particular sex [16,17]. In AR conditions, several studies [18][19][20] have shown a higher sensitivity in showing allergic responses in female mice compared to males, as evidenced by the higher concentrations of pro-inflammatory cytokines produced. This is the main reason for using female sex to see the molecular responses more clearly.…”
Section: Animalsmentioning
confidence: 99%